Amino Acid Mutations of OprD Protein in Pseudomonas aeruginosa After Meropenem Exposure - Evendi, Agus; Harlita, Tiara Dini; Azahra, Sresta (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Pseudomonas aeruginosa is a gram-negative pathogen associated with nosocomial infections and increased resistance to carbapenems, often linked to porin OprD inactivation. This study aimed to analyse amino acid substitutions in the OprD protein of two meropenem-sensitive Pseudomonas aeruginosa isolates (AK36 and AK237b) after 12 days of in vitro exposure to subinhibitory meropenem concentration (0.5 µg/mL). DNA was extracted at three time points (days 0, 5, and 12) and the oprD gene was sequenced using Sanger sequencing. Protein sequences were aligned and modelled using Swiss-Model to identify mutations and to assess structural changes. By day 12, AK36 had Gln67Lys and Gly68Ser substitutions, whereas AK237b had Glu169Lys. Structural modelling suggests these mutations may alter porin conformation and reduce membrane permeability. Despite no increase in the MIC, oprD expression was suppressed, indicating early adaptation. These findings support the hypothesis that prolonged meropenem pressure induces molecular changes that precede phenotypic resistance. This study highlights the importance of monitoring porin mutations as an early indicator of carbapenem resistance in clinical microbiology. This could help to improve antibiotic stewardship by identifying isolates at risk of developing resistance before it becomes clinically apparent.